Bicentennial and the COVID-19 pandemic: a reflection from the axiological percpective - Díaz Ylaquijo, Percy (2021)
The recognition of the human condition of the Andean, Amazonian and coastal society on the eve of the Bicentennial is still a fundamental problem, on the part of some people who exercise politics or perhaps it is pertinent to call it politicking, this action will always cause discomfort and instability to the citizens in our country. The lack of axiological praxis on the part of many citizens who hold political office is to be noted more clearly, but it is also inconceivable that some conservative sectors in our country are showing naivety, under the aphorism of being good men who defend democracy. The problem lies when these people within their discourse advertise fallacies and classify in a whimsical way people who do not share their same ideas. Finally, the defenders of democracy end up wanting to give orders to the institutions of the state, violating the autonomy of the powers of the state. Furthermore, it is stated that Peru, in the name of the Bicentennial, has been facing the problem of corruption and resisting the problem of the COVID-19 pandemic, so it is worth asking: How much progress has our country made in the political, economic and social fields during the 200 years?